MicroRNA dysregulation and non-muscle invasive bladder cancer prognosis - Andrew, Angeline S. (Cancer Epidemiol Biomarkers Prev, 2019)
BACKGROUND: The high rate of non-muscle invasive bladder cancer recurrence is a major challenge in patient management. microRNAs (miRNAs) functionally regulate tumor cell proliferation and invasion, and have strong potential as biomarkers, since they are robust to degradation. The objective of this project was to identify reproducible prognostic miRNAs in resected non-muscle invasive bladder tumor tissue that are predictive of the recurrent tumor phenotype. METHODS: We utilized patients diagnosed with primary non-muscle invasive bladder cancer in three independent cohorts for a biomarker discovery / validation approach. Baseline tumor tissue from patients with the clinically challenging, non-muscle invasive primary low stage, Ta high-grade and T1 tumors comprised the discovery cohort (n=38). We isolated the tumor tissue RNA and assessed a panel of ~800 microRNAs (miRNAs). RESULTS: miR-26b-5p was the top-ranking prognostic tumor tissue miRNA, with a time-to-recurrence Hazard Ratio (HR) 0.043 for levels above vs. below median, (adjusted p-value=0.0003). miR-26b-5p was related to a dose-response reduction in tumor recurrence, and levels above the median were also associated with reduced time-to-progression (adjusted p-value=0.02). We used two independent longitudinal cohorts that included both low-grade and high-grade Ta and T1 tumors for validation and found a consistent relationship between miR-26b-5p and recurrence and progression. CONCLUSIONS: Our results suggest that miR-26b-5p levels may be prognostic for non-muscle invasive bladder cancer recurrence, and can feasibly be assessed in baseline tumor tissue from a wide variety of clinical settings. IMPACT: Early identification of those non-muscle invasive bladder tumor patients with refractory phenotypes would enable individualized treatment and surveillance.